Experimental investigation on sodium leak behaviour through a pinhole. (May 2022) - Avinash, Ch.S.S.S.; Hemanth Rao, E.; Malarvizhi, B.; Kumar Das, Sanjay; Lydia, G.; Ponraju, D.; Athmalingam, S.; Venkatraman, B.
Highlights: Sodium leak rates through a pin hole defect in a typical purification & fill line of FBR has been determined. Sodium leak experiments were carried out at various oxygen concentrations as a function of driving pressure. Plugging of the leak path observed for oxygen concentration above 0.5% and driving pressures of upto 3 bar. No plugging observed for oxygen concentrations of ≤ 0.5% and for pressures ≥ 4 bar. Unplugging was observed between 450 °C & 480 °C and a pressure of 4 bar. Abstract: Sodium is most preferred coolant in Fast Breeder Reactors (FBR) due to its favourable neutronic and excellent heat transfer properties. However, when exposed to atmosphere, sodium reacts with oxygen and moisture resulting in sodium fire leading to rise in ambient temperature and release of harmful sodium oxide aerosols. Owing to this, prevention and early detection of sodium leak is of highest priority in the design of sodium systems. In all sodium systems, wire type leak detectors are provided for early detection of sodium leak. However, sodium leak from small defects such as hairline crack and pinholes may lead to oxidation of sodium and deposition of reaction products plugging the leak path. Such leaks may go undetected, cause local corrosion of structural material and may lead to sudden failure. Hence, investigation on sodium leaks from small openings is vital for sodium safety. Series of experiments were carried out to understand such sodium leak scenario through a small aperture simulating a pinhole defect. Sodium plugging phenomenon was studied at various oxygen concentrations from 0.5% to 3% in the leak zone, as a function of driving pressure. Conditions for unplugging were also established by varying sodium temperature and driving pressure, for plugged cases.